Differential regulation of sleep by blue, green, and red light in Drosophila melanogaster - Bond, Samuel M.; Peralta, Aaliyah J.; Sirtalan, Dilhan; Skeele, Dominic A.; Huang, Haoyang; Possidente, Debra R.; Vecsey, Christopher G. (Frontiers in Behavioral Neuroscience, 2024)
Exposure to blue-enriched light from electronic devices is an emergent disruptor of human sleep, especially at particular times of day. To better understand and effectively model this phenomenon, we investigated the effects of light color on sleep in Drosophila melanogaster. We measured sleep in red-eyed Canton-S (CS) and white-eyed w 1118 flies in baseline 12:12 light/dark conditions and experimental conditions with light-color (blue, red, or green) exposure for all 12 hours of daylight or 3 hours in the morning or evening. Blue light reduced daytime and nighttime sleep in CS but not in w 1118 , potentially indicating a role for the compound eye in blue light's effects on fruit fly sleep. Red light, especially in the evening, reduced sleep during exposure in both strains. Green light had minimal effects on sleep in CS flies, but evening exposure reduced sleep in w 1118 flies, mimicking red light's effects. In conclusion, light's effects on sleep in D. melanogaster are dependent on wavelength and time-of-day. Future studies will aim to dissect these mechanisms genetically.